1988
DOI: 10.1111/j.2042-7158.1988.tb05202.x
|View full text |Cite
|
Sign up to set email alerts
|

The emetic activity of centrally administered cisplatin in cats and its antagonism by zacopride

Abstract: Cisplatin administered by either the intravenous (i.v.) or intra-cerebroventricular (i.c.v.) route produced emesis in cats. The average time to onset of emesis was decreased significantly (4.0 min versus 100.6 min) when cisplatin was administered i.c.v. Zacopride administered either i.c.v. (0.02 mg) or i.v. (0.1 mg kg-1) completely blocked the emesis due to cisplatin given by either route. Their data show that cisplatin possesses a central emetic component and that this is blocked by zacopride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 5 publications
0
29
1
Order By: Relevance
“…It has previously been shown that injection of the 5-HT3 receptor antagonist, zacopride, into the fourth ventricle inhibits cisplatin-induced emesis (Smith et al, 1988). However, the present study is believed to be the first to demonstrate inhibition of cisplatin-induced emesis by discrete injections of a 5-HT3 receptor antagonist into the area postrema, the region containing the CTZ.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…It has previously been shown that injection of the 5-HT3 receptor antagonist, zacopride, into the fourth ventricle inhibits cisplatin-induced emesis (Smith et al, 1988). However, the present study is believed to be the first to demonstrate inhibition of cisplatin-induced emesis by discrete injections of a 5-HT3 receptor antagonist into the area postrema, the region containing the CTZ.…”
Section: Resultscontrasting
confidence: 45%
“…The precise mechanisms affected by the antagonists are unclear at present, although some clues may be derived from previous work with cisplatin. Intravenous injection of cisplatin induces emesis with a delay of approximately 60min and 100min in the ferret and cat respectively (Stables et al, 1987;Smith et al, 1988), whereas injection of cisplatin directly into the fourth ventricle of the cat caused emesis within 4min (Smith et al, 1988). Since the area postrema is outside the blood-brain barrier, intravenously injected cisplatin would be expected to make rapid contact with this structure.…”
Section: Resultsmentioning
confidence: 99%
“…The serotonin released would be metabolised within the intestine and/or on its passage through the liver, leading to increases both in plasma and urine of its main metabolite, (Smith et al, 1988) and the central administration of 5-HT3 antagonists prevents vomiting induced by cisplatinum (Higgins et al, 1989). The largest concentration of 5-HT3 receptors is present in the brain medulla in the nucleus tractus solitarious and area postrema regions, where the chemoreceptor trigger zone is located and where the vagal afferents enter the brain .…”
Section: Discussionmentioning
confidence: 99%
“…These re sults suggest that cisplatin acts mainly on peripheral sites. On the other hand, complete inhibition of cisplatin-induced emesis is observed following ablation of the area postrema, which is recognized as the che moreceptor trigger zone (CTZ) in cats and dogs (8,13), or injection of 5-HT3 receptor antagonists into the IVth ventricle in ferrets and cats (5,7), suggesting that the site of action may be central.…”
mentioning
confidence: 99%
“…A number of studies on the emetic response induced by cisplatin have been carried out in ferrets (1)(2)(3)(4)(5), cats (6)(7)(8), Suncus murinus (9, 10) and dogs (11)(12)(13). It seems to be clear that 5-HT3 receptors play an impor tant role in cisplatin-induced emesis, since it is strongly inhibited by 5-HT3 receptor antagonists such as ICS205930 (14) and MDL72222 (15) in all the species mentioned above (2-4, 7, 10-12).…”
mentioning
confidence: 99%